DISCHARGING ACCOUNTABILITY THROUGH GOVERNANCE: CASES FROM WAQF INSTITUTIONS IN INDONESIA - Ramli, Nathasa Mazna; Mohd Salleh, Nurul Husna; Muhamed, Nurul Aini (Online Journal of Research in Islamic Studies, 2015)
The ascendancy of Islamic finance particularly its offshoot, Islamic banking has been aggressive considering its spate of development. A salient factor responsible for this is the governing law for such financing paradigm. It is however contestable whether the workability of Islamic banking hinges on dedicated governing laws, amended subsisting laws or existing laws. In other words, is the existing legal (conventional) infrastructure adequate for any Islamic finance jurisdiction, or is there a need for a separate governing law? It is evident that this question is pertinent, vexed and has far-reaching implications. This article seeks to attend to this question in a very concise manner. Thus, the author forms an opinion common-sensibly resorting to comparative analysis, with or without judgements as well as real world country case studies.